If p_1,p+3,3p_1are in ap then pis equal to
Answers
Answered by
1
In Arithmetic sequence ,
2 × middle term = sum of remaining 2 terms
Here,
= > 2( p + 3 ) = ( p - 1 ) + ( 3p - 1 )
= > 2p + 6 = p - 1 + 3p - 1
= > 2p + 6 = p + 3p - 1 - 1
= > 2p + 6 = 4p - 2
= > 6 + 2 = 4p - 2p
= > 8 = 2p
![= \: > \frac{8}{2} = p = \: > \frac{8}{2} = p](https://tex.z-dn.net/?f=+%3D++%5C%3A++%26gt%3B++%5Cfrac%7B8%7D%7B2%7D++%3D+p)
= > 4 = p
![\boxed{ \boxed{ \boxed{ \textbf{ <br /> \underline{Hence, the value of of variable p is 4 }}}}} \boxed{ \boxed{ \boxed{ \textbf{ <br /> \underline{Hence, the value of of variable p is 4 }}}}}](https://tex.z-dn.net/?f=+%5Cboxed%7B+%5Cboxed%7B+%5Cboxed%7B++%5Ctextbf%7B++%3Cbr+%2F%3E+%5Cunderline%7BHence%2C+the+value+of+of+variable+p+is+4+%7D%7D%7D%7D%7D)
2 × middle term = sum of remaining 2 terms
Here,
= > 2( p + 3 ) = ( p - 1 ) + ( 3p - 1 )
= > 2p + 6 = p - 1 + 3p - 1
= > 2p + 6 = p + 3p - 1 - 1
= > 2p + 6 = 4p - 2
= > 6 + 2 = 4p - 2p
= > 8 = 2p
= > 4 = p
Similar questions